Understanding the Influence of Biochar Augmentation in Anaerobic Digestion by Principal Component Analysis - Jessica Quintana-Najera; A. John Blacker; Louise A. Fletcher; Andrew B. Ross (Energies, 2023)
Biochar addition in anaerobic digestion has been repeatedly reported to improve methane production, however, this ability is not well understood. This work aims to understand and correlate the most important factors influencing anaerobic digestion performance using principal component analysis along with quantitative and qualitative descriptive analysis to evaluate the variations of methane production with the addition of biochar. Reports from the literature using biochar produced from several feedstocks under variable pyrolysis conditions and therefore different compositions were carefully gathered and compared with their own non-biochar controls. Woody-derived biochars, produced at 450–550 °C, containing an ash content of 3.1–6.3%, and an O:C ratio of 0.20, were responsible for having the greatest positive effect. The amount of biochar added to the digesters also influences anaerobic digestion performance. Increasing biochar loads favours the production rate, although this can be detrimental to methane yields, thereby, biochar loads of approximately 0.4–0.6% (w/v) appear to be optimal. This work provides a guide for those interested in biochar augmentation in anaerobic digestion and identifies the main interactions between the variables involved.